Original articleHyperfractionation of HDR brachytherapy – influence on doses and biologically equivalent doses in clinical target volume and healthy tissues - Skowronek, Janusz; Zwierzchowski, Grzegorz; Piotrowski, Tomasz (Journal of Contemporary Brachytherapy, 2009)
Purpose: The aim of this work was to compare value of doses calculated in healthy tissues according to chosen different HDR brachytherapy (HDRBT) fractionation schemas with doses given once and twice daily. Material and methods: Fifty one patients with head and neck cancers, brain tumors, breast cancers, sarcoma, penile cancer and rectal cancer were qualified for calculations. Doses were calculated using PLATO planning system (Nucletron®) in chosen critical points in surrounded healthy tissues. For all treatment plans doses were compared using the BED (Biologically Equivalent Dose) formula. Data obtained from original PDR treatment plans were used for the elaboration of hypothetical HDRBT treatment plans – once and twice daily. For statistical analysis Wilcoxon test, Friedman ANOVA test and Kendall ratio were used. Results: One ascertained that the increase of the fraction dose from 4 Gy to 10 Gy caused the necessity to decrease the total dose in the treatment area (p < 0.001), in the greater degree after fractionation twice daily. In many examined critical points in organs at risk when the biological equivalence dose in the treatment area was the same, one ascertained the decrease of the total physical HDR dose according to the growth of the fraction dose. Similar dependences appeared also for biologically equivalent doses. Conclusions: The increase of the HDR fraction dose or the use of two fractions daily instead of one fraction per day causes the need to decrease the physical dose in the treatment calculations using BED formula and it should be valuable in choosing fractionation schema.